2005
DOI: 10.1159/000083860
|View full text |Cite
|
Sign up to set email alerts
|

Von Hippel-Lindau Disease – a Rare Disease Important to Recognize

Abstract: Introduction: Von Hippel-Lindau disease (VHL) is an autosomal dominant multisystemic cancer syndrome due to a mutation of the VHL tumor suppressor gene on chromosome 3, region p25-26, with an incidence of 1/36,000 in newborns. Patients are at risk of developing cerebellar, spinal and retinal hemangioblastoma, renal cell carcinoma, pheochromocytoma, pancreatic neuroendocrine tumors, pancreatic and renal cysts, and epididymal cystadenoma. The most common causes of death from VHL are metastases from renal cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Study of affected lineages revealed germ-line mutations in the APC gene responsible for familial adenomatous polyposis, and likely for predisposition to brain tumors, including glioma, and possibly a separate variant which has increased incidence of medulloblastoma. 20 Other familial neoplastic syndromes include Turcot's, 21 von HippelLindau disease, 22 Gorlin syndrome, 23 and multiple endocrine neoplasia syndromes. 24 There are numerous well-recognized hereditary syndromes that manifest with brain tumors as part of their phenotype.…”
Section: Results Relative Risksmentioning
confidence: 99%
“…Study of affected lineages revealed germ-line mutations in the APC gene responsible for familial adenomatous polyposis, and likely for predisposition to brain tumors, including glioma, and possibly a separate variant which has increased incidence of medulloblastoma. 20 Other familial neoplastic syndromes include Turcot's, 21 von HippelLindau disease, 22 Gorlin syndrome, 23 and multiple endocrine neoplasia syndromes. 24 There are numerous well-recognized hereditary syndromes that manifest with brain tumors as part of their phenotype.…”
Section: Results Relative Risksmentioning
confidence: 99%
“…ECc and spermatoceles are differentiated from acute or chronic epididymitis, hydroceles, varicoceles, extratesticular scrotal masses (lipomas, lymphangiomas), epididymal tumours (adenomatoid tumour), testicular tumours (9,10). ECs are associated defects in children with cystic fibrosis (11), von Hippel-Lindau disease (12), and polycystic kidney disease (13). An increased incidence of ECs has been reported in boys who are exposed in utero to diethylstilbestrol (14).…”
mentioning
confidence: 99%
“…Множественные гемангиобластомы, как пра-вило, поражают структуры задней черепной ямки, сетчатки и спинной мозг. Частота синдрома Гиппеля-Линдау у паци-ентов со спинальными гемангиобластомами составляет 20-40% [6,7].…”
Section: Department Of Nervous System Diseases Andunclassified